J-R type silicon carbide electrostatic chuck and preparation method thereof
By using SiC single crystal material to prepare the dielectric layer of the electrostatic suction cup, the problems of unstable thermal conductivity and insufficient corrosion resistance in the prior art are solved, and the electrostatic suction cup with high thermal conductivity and excellent corrosion resistance are achieved, which is suitable for semiconductor manufacturing. high temperature environment.
Patent Information
- Application Number
- CN202411239885.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-05
- Publication Date
- 2025-01-14
AI Technical Summary
The dielectric layer of the existing J-R type electrostatic suction cup has unstable thermal conductivity and insufficient corrosion resistance, which cannot meet the demand for high temperature and corrosion resistance in semiconductor manufacturing.
Using SiC single crystal as the dielectric layer material, the electrode layer is printed on the electrostatic suction cup ceramic matrix and co-fired with the SiC single crystal J-R layer to prepare J-R type silicon carbide static electricity with high thermal conductivity and excellent corrosion resistance. Suction cup.
It realizes high thermal conductivity and low dielectric loss of the electrostatic suction cup, and can be used at higher temperatures. Since SiC and silicon wafer are homologous materials, it avoids metal impurities contamination on the wafer and satisfies the modern industry's static electricity. Suction cup performance requirements.
Smart Images

Figure CN119314934A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of SiC materials, and in particular relates to a method for manufacturing a JR type electrostatic chuck of a dielectric layer by using SiC single crystal. Background Art
[0002] In the field of advanced large-scale integrated circuits and optics, when performing deposition, etching and detection processes, the wafer is transferred back and forth between various processes. At this time, the wafer needs to be fixed so that it can be placed stably and accurately in the process equipment. Under the precise manufacturing process requirements of such large-scale integrated and highly complex circuits, wafer clamping technology is particularly important. At present, the main wafer clamping methods include mechanical chucks, vacuum suction cups, electrostatic suction cups and other clamping methods. Among them, the mechanical fixation method is easy to scratch the wafer, and applying strong force to specific parts may cause the wafer to break. If vacuum adsorption is used, the decompression adsorption method like a suction cup cannot be used, and it is not suitable for vacuum environments. The electrostatic adsorption method has outstanding advantages such as controllable temperature, uniform and stable adsorption force, pollution-free adsorption, no scratches and wrinkles on the wafer during adsorption, no wafer edge exclusion effect, and suitability for vacuum environment. It is used as an important wafer clamping method in the modern semiconductor manufacturing industry and has become the core process of today's high-end ultra-large-scale integrated circuit equipment such as etcher (ETCH), ion implantation machine, chemical vapor deposition (CVD), physical vapor deposition (PVD) and other semiconductor manufacturing equipment. It is widely used in wafer manufacturing processes such as etching, chemical vapor deposition, and ion implantation in plasma and vacuum environments.
[0003] The main materials of common electrostatic chucks are mostly aluminum oxide (Al2O3) and aluminum nitride (AlN). Among them, Al2O3 has good physical strength, stable chemical properties and thermal stability, and low cost, and is mostly used in electronic packaging. However, its volume resistivity is large (generally higher than 1013Ω·cm), thermal conductivity is low, and the thermal conductivity drops rapidly with the increase of the weight percentage of glass components. When the weight of Al2O3 accounts for 90%, the thermal conductivity drops to 50% of the maximum value. In addition, the thermal expansion coefficient of Al2O3 is quite different from that of the wafer. As a packaging material, AlN has electrical properties (dielectric constant, volume resistivity, dielectric strength) and bending strength comparable to Al2O3, thermal conductivity is much higher than Al2O3, and thermal expansion coefficient is similar to that of wafers, but its thermal conductivity is a sensitive function of density. Even a small impurity concentration will cause a significant decrease in its thermal conductivity, which is more obvious when the impurity is oxygen. Therefore, when AlN is sintered, it is necessary to control the entry of oxygen impurities. In addition, with the development of market demand, electrostatic chucks are subject to stricter corrosion resistance standards than before. For example, during the etching process, the electrostatic chuck is exposed to a plasma environment with severe halogen corrosive gases (F, Cl, etc.), and even an electrostatic chuck made of AlN, Al2O3 or similar materials may not be able to successfully prevent corrosion. In addition, as the size of wafers gradually increases, the demand for temperature control uniformity increases, so it is necessary to further seek an alternative material with better corrosion resistance and thermal conductivity while meeting the electrical properties required by the electrostatic chuck.
[0004] Silicon carbide (SiC) is a compound formed by Si and C through covalent bonds. The strong covalent bonds of SiC give it many excellent properties such as high melting point, high hardness, high strength, stable chemical properties, small thermal expansion coefficient, high thermal conductivity, wear resistance, corrosion resistance, etc. It is widely used in many industrial fields such as precision machining, petrochemicals, transportation, aerospace, nuclear energy, etc. In addition, SiC materials have many advantages such as wide bandgap, high critical breakdown field strength, and high saturated electron drift rate, which make them widely used in high-temperature, high-frequency, high-power, and radiation-resistant semiconductor components. It has great application prospects in the semiconductor industry, and single-crystal SiC is called the third-generation semiconductor material. Compared with AlN and Al2O3, SiC has smaller density and thermal expansion coefficient, better thermal conductivity, and smaller dielectric loss. At the same time, it is easy to form a SiO2 protective film on its surface, and it has better corrosion resistance. More importantly, SiC is used as the manufacturing material of the dielectric layer (also known as the JR layer) of the JR-type electrostatic chuck, which is the same source material as the wafer, and will not introduce a large amount of additional metal impurities to pollute the silicon wafer. Pure SiC is usually a semiconductor or even an insulating material, but general SiC powder or SiC ceramics inevitably contain a large amount of conductive impurities or additives, which makes the volume resistivity of SiC not high, usually lower than the range required by the JR layer.
[0005] Therefore, it is necessary to increase the volume resistivity of SiC to meet the use requirements of electrostatic chucks. The excellent comprehensive properties of silicon carbide make it a potential application prospect in the field of electrostatic chucks, but the advantages of silicon carbide have not been reflected in this field. Summary of the invention
[0006] In view of the technical problems that the thermal conductivity of the dielectric layer in the existing JR type electrostatic chuck is unstable and the corrosion resistance needs to be enhanced, the present invention aims to provide a method for manufacturing a JR type electrostatic chuck with a dielectric layer using SiC single crystal. Compared with polycrystalline SiC, single crystal SiC does not have grain boundary corrosion and has fewer defects accordingly, and can effectively resist corrosion in a plasma environment to meet the application needs of the semiconductor industry.
[0007] In a first aspect, the present invention provides a method for preparing a JR type silicon carbide electrostatic chuck, the preparation method comprising the following steps: (1) printing an electrode layer on an electrostatic chuck ceramic substrate to obtain a substrate-electrode layer structure; (2) A SiC single crystal JR layer is connected to one side of the electrode layer of the substrate-electrode layer structure, and the JR-type silicon carbide electrostatic chuck is obtained by hot pressing and co-firing.
[0008] Preferably, the electrostatic chuck ceramic substrate is SiC ceramic, Al2O3 ceramic or AlN ceramic; wherein the preparation method of the electrostatic chuck ceramic substrate comprises the following steps: mixing SiC raw material powder, Al2O3 raw material powder or AlN raw material powder with a sintering aid, and sequentially subjecting the mixture to molding, degreasing and sintering; The sintering aid includes at least one of the rare earth oxides Y2O3, CeO2, Sm2O3, and Er2O3; wherein the total mass of the sintering aid is controlled to be no less than 1% of the total mass of the SiC raw material powder, the Al2O3 raw material powder or the AlN raw material powder and the sintering aid mixed powder, preferably no less than 5%.
[0009] Preferably, the molding method is dry pressing molding followed by isostatic pressing molding, tape casting molding or gel injection molding; wherein, in the dry pressing molding followed by isostatic pressing molding, the dry pressing pressure is not less than 20 MPa, the holding time is not less than 10 s, the isostatic pressing pressure is not less than 150 MPa, and the holding time is not less than 120 s; The sintering includes hot pressing sintering, normal pressure liquid phase sintering or plasma sintering; wherein, the temperature of the hot pressing sintering is not less than 1400°C, preferably not less than 1600°C, the pressure is not less than 20MPa, preferably not less than 30MPa, the sintering time is not less than 1h, and the protective atmosphere is Ar atmosphere; in the normal pressure liquid phase sintering, the sintering temperature is not less than 1500°C, preferably not less than 1800°C, the sintering time is not less than 2h, and the protective atmosphere is Ar atmosphere; in the plasma sintering, the sintering temperature is not less than 1500°C, preferably not less than 1700°C, the sintering pressure is not less than 20MPa, and the sintering time is not less than 4min, preferably not less than 10min.
[0010] Preferably, the printing preparation method of the electrode layer is screen printing, and the electrode layer is an Ag paste electrode or an Ag-Cu-Ti electrode; preferably, the thickness of the electrode layer is 0.1-0.2 mm.
[0011] Preferably, the preparation process of the SiC single crystal JR layer includes: First, a crucible containing SiC powder is placed in a growth chamber of a crystal growth furnace and a heat preservation felt is arranged around the crucible; then, the growth chamber is evacuated and a flushing gas is introduced to flush and remove impurities from the growth chamber, the crucible and the heat preservation felt; Finally, a physical vapor phase PVT method is used to grow a SiC single crystal, and the SiC single crystal JR layer is obtained through slicing.
[0012] Preferably, the SiC powder is a high-purity SiC powder with a purity greater than or equal to 99.999% or a SiC powder doped with a trace amount of deep energy level elements, preferably a SiC powder doped with a trace amount of deep energy level elements; The deep level elements include Group IB to Group VIIIB elements, preferably vanadium or titanium; The doping concentration of the SiC powder doped with trace deep energy level elements is 1×10 15 ~1×10 17 cm -3 1×10 16 ~1×10 17 cm -3 Magnitude.
[0013] Preferably, in the flushing and impurity removal: the flushing gas includes at least one of an inert gas, H2, and CH4, preferably Ar; the flushing time is not less than 200 min, the flushing temperature is not less than 2000°C, the flushing gas pressure is not less than 30000 Pa, and the flushing flow rate is not less than 2000sccm; preferably, the flushing time is 400-600 min, the flushing temperature is 2300-2500°C, the flushing gas pressure is 40000-50000 Pa, and the flushing flow rate is 2500-3000sccm.
[0014] Preferably, the growth temperature of the crystal growth by the physical vapor phase PVT method is not less than 2200° C., and the growth pressure is not less than 500 Pa; The thickness of the SiC single crystal JR layer is 1-2 mm, and the volume resistivity is 10 8 ~10 13 Ω·cm, preferably 10 8 ~10 12 Ω·cm.
[0015] Preferably, the temperature of the hot-pressing co-firing is not less than 800° C., the pressure is not less than 0.1 MPa, and the time of the hot-pressing co-firing is not less than 1 hour.
[0016] In a second aspect, the present invention provides a JR type silicon carbide electrostatic chuck obtained according to the above-mentioned preparation method.
[0017] Beneficial Effects The present invention provides an electrostatic chuck with excellent corrosion resistance and thermal properties and controllable volume resistivity. Compared with the current Al2O3 and AlN ceramic electrostatic chucks, the electrostatic chuck JR layer is made of single crystal SiC, which has higher and more stable thermal conductivity and smaller dielectric loss. Due to its high melting point, the prepared electrostatic chuck can be used at a higher temperature. Moreover, SiC and silicon wafers are homologous materials, and no additional large metal impurities are introduced to contaminate the wafers. Its excellent comprehensive performance better meets the performance requirements of modern industrial fields for electrostatic chucks. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 Schematic diagram of the prototype and electrode layer pattern of the JR type silicon carbide electrostatic chuck according to the example of the present invention. DETAILED DESCRIPTION
[0019] The present invention is further described below by the following embodiments. It should be understood that the following embodiments are only used to illustrate the present invention, but not to limit the present invention.
[0020] The following, combined Figure 1 , exemplarily illustrating the preparation method of the JR type silicon carbide electrostatic chuck provided by the present invention. The preparation method may include the following steps: (1) printing an electrode layer on an electrostatic chuck ceramic substrate (base layer) to obtain a substrate-electrode layer structure; (2) A SiC single crystal JR layer is connected to one side of the electrode layer of the substrate-electrode layer structure, and the JR-type silicon carbide electrostatic chuck is obtained by hot pressing and co-firing.
[0021] In some embodiments, the electrostatic chuck ceramic substrate (base layer) may be SiC ceramic, Al2O3 ceramic or AlN ceramic; wherein, the preparation method of the electrostatic chuck ceramic substrate may include the following steps: mixing SiC raw material powder, Al2O3 raw material powder or AlN raw material powder with a sintering aid, and sequentially subjecting the mixture to molding, degreasing and sintering.
[0022] In some embodiments, the sintering aid may include at least one of the rare earth oxides Y2O3, CeO2, Sm2O3, and Er2O3. This type of aid can effectively enhance the corrosion resistance of the above-mentioned ceramic sintered body and reduce the service damage of the above-mentioned ceramic in an environment such as plasma etching. In order to ensure the sintering quality of the ceramic, the total mass of the sintering aid is controlled to be not less than 1% of the total mass of the SiC raw material powder, Al2O3 raw material powder or AlN raw material powder and the sintering aid mixed powder, and preferably not less than 5%.
[0023] In some embodiments, the molding method can be dry pressing molding followed by isostatic pressing molding, cast molding or gel injection molding; wherein, in the dry pressing molding followed by isostatic pressing molding, the dry pressing pressure is not less than 20MPa, the holding time is not less than 10s, the isostatic pressing pressure is not less than 150MPa, and the holding time is not less than 120s.
[0024] In some embodiments, the sintering may include hot pressing sintering, normal pressure liquid phase sintering or plasma (SPS) sintering; wherein, the temperature of the hot pressing sintering is not less than 1400°C, preferably not less than 1600°C, the pressure is not less than 20MPa, preferably not less than 30MPa, the sintering time is not less than 1h, and the protective atmosphere is Ar atmosphere; in the normal pressure liquid phase sintering, the sintering temperature is not less than 1500°C, preferably not less than 1800°C, the sintering time is not less than 2h, and the protective atmosphere is Ar atmosphere; in the plasma sintering, the sintering temperature is not less than 1500°C, preferably not less than 1700°C, the sintering pressure is not less than 20MPa, and the sintering time is not less than 4min, preferably not less than 10min.
[0025] In some embodiments, the thickness of the electrostatic chuck ceramic substrate may be 10-15 mm.
[0026] In some embodiments, the printing preparation method of the electrode layer can be screen printing, and the electrode layer can be an Ag paste electrode or an Ag-Cu-Ti electrode; preferably, the thickness of the electrode layer can be 0.1-0.2 mm.
[0027] In some embodiments, the preparation process of the SiC single crystal JR layer may include the following steps: First, a crucible containing SiC powder is placed in a growth chamber of a crystal growth furnace and a heat preservation felt is arranged around the crucible; then, the growth chamber is evacuated and a flushing gas is introduced to flush and remove impurities from the growth chamber, the crucible and the heat preservation felt; Finally, a physical vapor phase PVT method is used to grow a SiC single crystal, and the SiC single crystal JR layer is obtained through slicing.
[0028] In some embodiments, the SiC powder can be a high-purity SiC powder with a purity greater than or equal to 99.999% or a SiC powder doped with a trace amount of deep energy level elements, preferably a SiC powder doped with a trace amount of deep energy level elements. The externally doped deep energy level elements can form a compensation effect with the shallow energy level impurity elements (N, P, B, Al, etc.) contained in the SiC itself, which is beneficial to improve the volume resistivity of the SiC single crystal finally prepared.
[0029] In some embodiments, the deep level element may include an element of Group IB to Group VIIIB, preferably vanadium or titanium.
[0030] Considering that high concentration deep level elements are prone to form precipitation defects during crystal growth (the solid solubility limit of vanadium is 5×10 17 cm -3 ), which is not conducive to the final crystal quality, while the compensation effect formed by too low doping concentration is weak, which is not conducive to achieving the semi-insulating characteristics of SiC single crystal. Therefore, in some embodiments, the doping concentration of the SiC powder doped with trace deep energy level elements is controlled to be 1×10 15 ~1×10 17 cm -3 1×10 16 ~1×10 17 cm -3 Magnitude.
[0031] In some embodiments, in the flushing and impurity removal: the flushing gas may include at least one of an inert gas, H2, and CH4, preferably Ar; the flushing time is not less than 200 min, the flushing temperature is not less than 2000°C, the flushing gas pressure is not less than 30000 Pa, and the flushing flow rate is not less than 2000sccm; preferably, the flushing time is 400-600 min, the flushing temperature is 2300-2500°C, the flushing gas pressure is 40000-50000 Pa, and the flushing flow rate is 2500-3000sccm.
[0032] In some embodiments, the growth temperature of the crystal growth by the physical vapor phase PVT method is not less than 2200° C., and the growth pressure is not less than 500 Pa.
[0033] In some embodiments, the thickness of the SiC single crystal JR layer may be 1-2 mm, and the volume resistivity in the range of room temperature to 250° C. may be 10 8 ~10 13 Ω·cm, preferably 10 8 ~10 12 Ω·cm.
[0034] In some embodiments, the temperature of the hot-pressing co-firing is not less than 800° C. and not higher than the melting point of the electrode material used, the pressure is not less than 0.1 MPa, and the time of the hot-pressing co-firing is not less than 1 hour.
[0035] SiC single crystal has extremely high thermal conductivity, with a thermal conductivity of up to 320-490 W·m -1 ·K -1 The structure is uniform and single, and the comprehensive performance is better than that of polycrystalline SiC ceramic materials. Therefore, the use of SiC single crystal material to prepare the JR layer of the electrostatic chuck can effectively improve the overall performance of the device. Moreover, the JR type silicon carbide single crystal electrostatic chuck obtained by the preparation method provided by the present invention can make the volume resistivity of the JR layer within the range of room temperature to 250°C within 10 8 -10 12 Ω·cm, and has excellent mechanical and thermal properties. The thermal conductivity of the JR layer is not less than 320W·m -1 ·K -1 After chemical etching in a hydrofluoric acid-simulated plasma etching environment, the point defect and dislocation density does not exceed 2300 cm -2 .
[0036] The following further examples are given to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention all belong to the scope of protection of the present invention. The specific process parameters of the following examples are also only examples within a suitable range, that is, those skilled in the art can make selections within a suitable range through the description of this article, and are not limited to the specific values exemplified below. If not specifically stated, the technical means used in the embodiments are conventional means well known to those skilled in the art.
[0037] Example 1
[0038] The method for preparing the JR type silicon carbide electrostatic chuck provided in this embodiment comprises the following steps: (1) 95 wt% of Al2O3 raw material powder with an average particle size of 0.2 μm, 3 wt% of Y2O3, and 2 wt% of Ce2O3 are added in proportion to prepare a ceramic powder, 1 wt% of the total mass of the ceramic powder is added as a dispersant stearic acid and 5 wt% of a binder, anhydrous ethanol is used as a solvent, and ball milling is performed at a speed of 300 rpm for 12 h to obtain a uniformly mixed liquid slurry, the obtained mixed slurry is placed in an oven and dried at a temperature of 60°C for 24 h, the dried slurry is crushed by a crusher and then sieved through a 100-mesh sieve, and after sieving, it is formed and debonded, and then hot-pressed sintering is performed for densification, and the sintering process parameters are 1800°C, 20 MPa, and 4 h to obtain an electrostatic chuck ceramic matrix; The screen printing process is adopted to first make a printing plate, and then print a conductive silver paste with a thickness of 0.1 mm on the substrate prepared in step (1), and then dry and integrate them to obtain a substrate-electrode layer structure. (2) A crucible containing SiC powder (without doping) was placed in a growth chamber in a crystal growth furnace. A heat-insulating felt was arranged around the crucible. The growth chamber was evacuated and then filled with Ar gas, a protective gas required for growing a single crystal, to a pressure of 60,000 Pa. The temperature was raised to 2,100°C and flushing gas Ar gas was introduced with a gas flow rate of 4,000 sccm for a flushing time of 200 min. The temperature was then raised to 2,300°C and the pressure was reduced to 1,000 Pa for crystal growth. The grown SiC single crystal was sliced to obtain a SiC single crystal JR layer, and its median resistivity was measured to be 4.7×10 8 Ω·cm; The substrate containing the electrode layer and the JR layer are connected together by hot pressing co-firing, and the process parameters are 800° C., 0.2 MPa, and 2 h to obtain the JR type silicon carbide electrostatic chuck.
[0039] Example 2
[0040] The preparation method of the JR type silicon carbide electrostatic chuck provided in this embodiment refers to that in embodiment 1, the main difference is that: in step (1), 95wt% SiC raw material powder with an average particle size of 0.5μm, 3wt% Y2O3, and 2wt% Er2O3 are added in proportion to prepare a ceramic powder, to which 5wt% of the total mass of the ceramic powder as a dispersant stearic acid and 5wt% of a binder are added; room temperature liquid phase sintering is performed for densification, and the sintering process parameters are 1960°C and 3h; In step (2), the growth material is doped with 8.2×10 15 cm -3 The vanadium-SiC mixed powder was rinsed and impurity-removed at a temperature of 2300°C and a rinsing time of 300 min. The median resistivity of the SiC single crystal after slicing was 6.2×10 10 Ω·cm; the process parameters of hot pressing co-firing are 800℃, 0.5MPa, 1h.
[0041] Example 3
[0042] The preparation method of the JR type silicon carbide electrostatic chuck provided in this embodiment refers to that in embodiment 1, the main difference is that: in step (1), firstly, 95wt% of AlN raw material powder with an average particle size of 0.5μm, 3wt% of Y2O3, and 2wt% of Er2O3 are added in proportion to prepare a ceramic powder, to which 5wt% of the total mass of the ceramic powder as a dispersant stearic acid and 5wt% of a binder are added; SPS sintering is performed for densification, and the sintering process parameters are 1500°C, 20MPa, and 6min; In step (2), the growth material is doped with 5.2×10 16 cm -3 The temperature of rinsing and removing impurities of vanadium-SiC mixed powder is 2500℃; the crystal growth pressure is 2500Pa; the median resistivity of SiC single crystal after slicing is 1.1×10 11 Ω·cm; the process parameters of hot pressing co-firing are 800℃, 0.2MPa, 1h.
[0043] Example 4
[0044] The preparation method of the JR type silicon carbide electrostatic chuck provided in this embodiment is similar to that in embodiment 2, the main difference is that in step (2), the growth raw material is doped with 1.0×10 17 cm -3 The median resistivity of the vanadium-SiC mixed powder and SiC single crystal after slicing is 2.3×10 12 Ω·cm.
[0045] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as a limitation of the present invention. After reading the above content, it will be apparent to those skilled in the art that various modifications and substitutions of the present invention will occur. Therefore, the protection scope of the present invention should be limited by the appended claims.
Claims
1. A method for preparing a JR type silicon carbide electrostatic chuck, characterized in that: The preparation method comprises the following steps: (1) printing an electrode layer on an electrostatic chuck ceramic substrate to obtain a substrate-electrode layer structure; (2) A SiC single crystal JR layer is connected to one side of the electrode layer of the substrate-electrode layer structure, and the JR-type silicon carbide electrostatic chuck is obtained by hot pressing and co-firing.
2. The preparation method according to claim 1, characterized in that: The electrostatic chuck ceramic substrate is SiC ceramic, Al2O3 ceramic or AlN ceramic; wherein the preparation method of the electrostatic chuck ceramic substrate comprises the following steps: mixing SiC raw material powder, Al2O3 raw material powder or AlN raw material powder with a sintering aid, and sequentially subjecting the mixture to molding, degreasing and sintering; The sintering aid includes at least one of the rare earth oxides Y2O3, CeO2, Sm2O3, and Er2O3; wherein the total mass of the sintering aid is controlled to be no less than 1% of the total mass of the SiC raw material powder, the Al2O3 raw material powder or the AlN raw material powder and the sintering aid mixed powder, preferably no less than 5%.
3. The preparation method according to claim 1 or 2, characterized in that: The molding method is dry pressing molding followed by isostatic pressing molding, tape casting molding or gel injection molding; wherein, in the dry pressing molding followed by isostatic pressing molding, the dry pressing pressure is not less than 20 MPa, the holding time is not less than 10 s, the isostatic pressing pressure is not less than 150 MPa, and the holding time is not less than 120 s; The sintering includes hot pressing sintering, normal pressure liquid phase sintering or plasma sintering; wherein, the temperature of the hot pressing sintering is not less than 1400°C, preferably not less than 1600°C, the pressure is not less than 20MPa, preferably not less than 30MPa, the sintering time is not less than 1h, and the protective atmosphere is Ar atmosphere; in the normal pressure liquid phase sintering, the sintering temperature is not less than 1500°C, preferably not less than 1800°C, the sintering time is not less than 2h, and the protective atmosphere is Ar atmosphere; in the plasma sintering, the sintering temperature is not less than 1500°C, preferably not less than 1700°C, the sintering pressure is not less than 20MPa, and the sintering time is not less than 4min, preferably not less than 10min.
4. The preparation method according to any one of claims 1 to 3, characterized in that The printing preparation method of the electrode layer is screen printing, and the electrode layer is an Ag paste electrode or an Ag-Cu-Ti electrode; preferably, the thickness of the electrode layer is 0.1-0.2 mm.
5. The preparation method according to any one of claims 1 to 4, characterized in that: The preparation process of the SiC single crystal JR layer includes: First, a crucible containing SiC powder is placed in a growth chamber of a crystal growth furnace and a heat-insulating felt is arranged around the crucible; Then, the growth chamber is evacuated and flushing gas is introduced to flush and remove impurities from the growth chamber, the crucible, and the insulation felt; Finally, a physical vapor phase PVT method is used to grow a SiC single crystal, and the SiC single crystal JR layer is obtained through slicing.
6. The preparation method according to any one of claims 1 to 5, characterized in that: The SiC powder is a high-purity SiC powder with a purity greater than or equal to 99.999% or a SiC powder doped with a trace amount of deep energy level elements, preferably a SiC powder doped with a trace amount of deep energy level elements; The deep level elements include Group IB to Group VIIIB elements, preferably vanadium or titanium; The doping concentration of the SiC powder doped with trace deep energy level elements is 1×10 15 ~1×10 17 cm -3 1×10 16 ~1×10 17 cm -3 Magnitude.
7. The preparation method according to any one of claims 1 to 6, characterized in that: In the flushing and impurity removal: the flushing gas includes at least one of an inert gas, H2, and CH4, preferably Ar; the flushing time is not less than 200 min, the flushing temperature is not less than 2000°C, the flushing gas pressure is not less than 30000 Pa, and the flushing flow rate is not less than 2000sccm; preferably, the flushing time is 400-600 min, the flushing temperature is 2300-2500°C, the flushing gas pressure is 40000-50000 Pa, and the flushing flow rate is 2500-3000sccm.
8. The preparation method according to any one of claims 1 to 7, characterized in that: The physical vapor phase PVT method is used for crystal growth at a growth temperature of not less than 2200° C. and a growth pressure of not less than 500 Pa. The thickness of the SiC single crystal JR layer is 1-2 mm, and the volume resistivity is 10 8 ~10 13 Ω·cm, preferably 10 8 ~10 12 Ω·cm.
9. The preparation method according to any one of claims 1 to 8, characterized in that: The temperature of the hot-pressing co-firing is not less than 800° C., the pressure is not less than 0.1 MPa, and the time of the hot-pressing co-firing is not less than 1 hour.
10. A JR type silicon carbide electrostatic chuck obtained by the preparation method according to any one of claims 1 to 9.